2021
DOI: 10.21315/jps2021.32.3.7
|View full text |Cite
|
Sign up to set email alerts
|

The Physical and Mechanical Properties of Corn-based Bioplastic Films with Different Starch and Glycerol Content

Abstract: Petroleum-based plastics have had a long history with varied materials and applications. However, the major drawback with these plastics is their harmful impact on the environment. Poor disposal management of these plastics have ultimately affected humans. Therefore, starch-based bioplastics have been widely used because of their renewability, sustainability and cost-effectiveness. This work investigated the effect of different concentrations of corn starch (10%, 15%, and 20% w/w of distilled water) and glycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…It was decreased when the concentration of PLA was decreased and the concentration of CF was increased. This similar result was found in the previous study which showed that increasing the concentration of starch caused a reduction of elongation of break [28]. In addition, decrease elongation at break of FG-plasticized films was occurred when the plasticizer concentration was increased [31].…”
Section: Elongation At Breaksupporting
confidence: 90%
See 2 more Smart Citations
“…It was decreased when the concentration of PLA was decreased and the concentration of CF was increased. This similar result was found in the previous study which showed that increasing the concentration of starch caused a reduction of elongation of break [28]. In addition, decrease elongation at break of FG-plasticized films was occurred when the plasticizer concentration was increased [31].…”
Section: Elongation At Breaksupporting
confidence: 90%
“…This result is showed linear character with the physical and mechanical properties of corn-based bioplastics films with different starch and glycerol content, which demonstrated that the concentration of starch increased, with the increasing of tensile strength [28]. Furthermore, corn-based films with 10 % concentration of corn starch and glycerol possessed poor tensile strength at 0.5 MPa.…”
Section: Mechanical and Physical Properties Of Bioplastics Pla/cf Ten...mentioning
confidence: 74%
See 1 more Smart Citation
“…They reported that the addition of HS extract strengthened the hydrogen (H)‐bonding in the composites; therefore, the strengthened H‐bonding among the extract and chains, the steric hindrance, and the free volume between starch–starch chains were reflected in the decreased stiffness for all composites. [ 45,47,49 ] In our case, the HS fiber could mainly modify the starch–starch intermolecular interaction. There was strengthened H‐bonding among starch–HS fibers, with a reduction in the H‐bonding among the starch–starch fibers.…”
Section: Resultsmentioning
confidence: 74%
“…Pati sebagai bahan baku bioplastik memiliki keuntungan jumlahnya berlimpah, harga murah, dan dapat diperbaharui [4]. Namun, bioplastik berbahan dasar pati memiliki kekurangan yaitu bersifat tidak tahan air, rapuh, dan kaku [5].…”
Section: Pendahuluanunclassified